STRATEGI PENGEMBANGAN INFORMASI PENYULUHAN PERTANIAN MELALUI PROGRAM SIMLUHTAN DI KABUPATEN SLEMAN - Hermawan, Hermawan; Winarno, Joko; Windrati, Anita (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2017)
This study aims to analyse internal and external factors into strengths, weaknesses, opportunities, and threats and formulate an alternative strategy development of Agricultural extension information through Simluhtan Program in Sleman District. The research method is qualitative method with deep description strategy. The research location was UPT BP3K (Agricultural Extension Offices at Sub-District Level) in Sleman. Location determination was selected purposively, and data collection is done by deep interview, literature, and documentation. The results show the strength of the Simluhtan program is its online presence, availability of fast and accurate related facilities and administrator, while the weakness is the remote BP3K location, lack of administrator and officers on duty, lack of data update as well as coordination. Opportunities that can be utilized for the sustainability of the program is the accessible data online, the existence of government policy in institutional development of Agricultural Extension towards Sleman Smart City, easier and more efficient information technology, the need for data accuracy, while the threats are the existence of hackers, lack of coordination in the shift of the system from the central government, as well as decrease in numbers of extension officers as the main actors. Strategies that can be proposed is related to human resources development in terms of information technology, extension institutional development and the extension officers ability in implementing the programs, and development of support facilities connected to the Internet.